1999
DOI: 10.1161/01.cir.100.24.2406
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate Reductase Genotypes and Early-Onset Coronary Artery Disease

Abstract: Homozygosity for the 677C-->T mutation of MTHFR is common and is associated with an increased risk of premature CAD in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
1
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 24 publications
5
28
1
1
Order By: Relevance
“…Our findings support the view that TT MTHFR is an important risk factor for premature CHD in Europeans. 15,18,31 We found that elevated plasma homocysteine concentrations in Indian Asian, compared with European, white controls, were explained by their low folate and B 12 concentrations. In contrast, homocysteine concentrations in Indian Asian and European white CHD patients, compared with controls, were only partially accounted for by differences in age, creatinine, vitamin status, and MTHFR genotype.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Our findings support the view that TT MTHFR is an important risk factor for premature CHD in Europeans. 15,18,31 We found that elevated plasma homocysteine concentrations in Indian Asian, compared with European, white controls, were explained by their low folate and B 12 concentrations. In contrast, homocysteine concentrations in Indian Asian and European white CHD patients, compared with controls, were only partially accounted for by differences in age, creatinine, vitamin status, and MTHFR genotype.…”
Section: Discussionmentioning
confidence: 75%
“…More recent data show a significantly higher frequency of homozygosity for the MTHFR 677T mutation in patients with early-onset CHD than in patients with later-onset CHD or in control subjects. 31 The odds ratio for CHD in the young has been reported as 2.4 (95% CI, 1.2 to 4.7). 31 In the present study, we found that the prevalence of homozygosity for MTHFR 677T was higher in European white cases with onset of CHD before the age of 50 years compared with controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Other studies also support the notion that hyperhomocysteinemia is considered an independent risk factor for vascular disease: it has been demonstrated in the Physicians' Health Study,I in the European Concerted Action Project,I') and recently in a study that demonstrated that the homozygosity for the 677C) T mutation of methylenetetrahydrofolate reductase is common and is associated with an increased risk of premature CAD in this population. 20 The role of homocysteine in atherogenesis and progression of vascular disease is unknown. Several mechanisms were suggested, among them procoagulant effects.…”
Section: Discussionmentioning
confidence: 99%
“…Ambos os polimorfismos do gene MTHFR foram considerados fatores de risco para DAC 7,8,9,10 . A associação do polimorfismo MTHFR C677T com DAC foi confirmada por alguns estudos, nos quais a prevalência de portadores do alelo alterado foi maior no grupo DAC em relação aos controles [10][11][12][13][14] por outro lado, outros trabalhos não confirmam tal associação 15,16,17 .…”
Section: Introductionunclassified